Fine‐needle aspiration cytology in head and neck diagnosis. Issue 3 (7th February 2019) - Tempesta, Angela; Limongelli, Luisa; Capodiferro, Saverio; Maiorano, Eugenio; Favia, Gianfranco
Key Clinical Message: The proper performing of the fine‐needle aspiration cytology of head and neck neoplasms leads to an accurate preoperative diagnosis by an inexpensive and relatively simple technique. Abstract : The proper performing of the fine‐needle aspiration cytology of head and neck neoplasms leads to an accurate preoperative diagnosis by an inexpensive and relatively simple technique.